Long-Lasting Cigarette Smoking Alterations in Immune Function Occur in Cannabis Smokers, Possibly Rendering Them Vulnerable to Smoking-Related Tumors in Later Life - Lehrer, Steven; Rheinstein, Peter (American journal of clinical oncology, 2025)
Active cigarette smoking leads to increased CXCL5 production. CXCL5 mediates the immune response by attracting immune cells to areas of inflammation. Elevated CXCL5 levels are associated with various inflammatory diseases and tumorigenesis. In addition, smoking is linked to an increase in the level of the cytokine CEACAM6 in the bloodstream of smokers. CEACAM6 is increased in pancreatic adenocarcinoma, breast cancer, non-small-cell lung cancer, gastric cancer, colon cancer, and other cancers and promotes tumor progression, invasion, and metastasis. Although cytokine secretion in the innate immune response returns to nonsmoker levels after quitting smoking, the effects on the adaptive response appear to persist for years or decades due to epigenetic memory. As a result, epigenetic changes induced by smoking may contribute to long-lasting alterations in immune function, including elevated CXCL5 and CEACAM6. The effects of cannabis smoking might be similar. In the current study we used UK Biobank (UKB) data to assess the relationship of CXCL5, CEACAM6, and pulmonary function to cigarette and cannabis smoking. Our UK Biobank application was approved as UKB project 57245 (S.L. and P.H.R.). Our analysis included all subjects with smoking and/or marijuana use data in the UK Biobank database. Circulating levels of CXCL5 and CEACAM6 were from UKB Olink data. Individual CXCL5 and CEACAM6 levels are NPX, Normalized Protein expression, Olink arbitrary unit in Log2 scale (Olink Proteomics AB, Uppsala, Sweden; http://www.olink.com ). Current smokers and past smokers had elevated circulating levels of CXCL5 and CECAM6. In multivariate analysis, current, past, or no smoking history was significantly related to CXCL5 level and CECAM6 levels, independent of the effects of age, sex. Frequency of cannabis use had a similar effect. In multivariate analysis, frequency of cannabis use was significantly related to CXCL5 level and CECAM6 levels, independent of the effects of age, sex, and years between last cannabis use and enrollment in study. We can confirm a previous report of epigenetic changes induced by cigarette smoking that may contribute to long-lasting alterations in immune function related to CXCL5 and CEACAM6. In addition, we have found that these same long-lasting smoking alterations in immune function related to CXCL5 and CEACAM6 occur in cannabis smokers, possibly rendering them vulnerable to smoking-related tumors in later life.